Moving source geolocation algorithm and performance analysis using dual-satellites sequence measurements and calibration sources - Ding WANG; Li ZHANG; Ying WU (Tongxin xuebao)
The method for locating a moving source on earth using a sequence of time difference of arrival(TDOA)and frequency difference of arrival(FDOA)measurements pairs obtained by dual-satellites was presented in the presence of calibration sources with accurate positions.First,the difference calibration(DC)location algorithm aiming to the mobile target was derived,and its theoretical performance was also analytically derived.The result demonstrates that the DC localization variance could not reach the CRB,although it could eliminate the location bias produced by the position and velocity errors of the dual-satellites.For this reason,a two-step optimal association location algorithm was proposed,and its theoretical performance was proved to be equal to the CRB.Finally,a variety of numerical experiments are performed to corroborate the superiority of the geolocation algorithms and the effectiveness of the performance analysis.